ANALISIS IMPLEMENTASI PSAK 101 PADA LAPORAN KEUANGAN DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) - Indriaty, Novica; Nurul Fazira, Ajeng; Satria, Hendy; As Sahara, Masyitah; Kurnia, Sri (LPPM Universitas Bina Bangsa, 2025)
The Indonesian Accountants Association (IAI) issues accounting standards regarding financial reports for zakat, infaq and alms. This standard is contained in Statement of Financial Accounting Standards Number 101 which discusses financial reporting of zakat, infaq and alms. This research was conducted at BAZNAS for the period 2021 and 2022. The aim of this research was to find out whether the accounting treatment of zakat, infaq and alms funds by BAZNAS was in accordance with PSAK Number 101. The data analysis method used was qualitative. The result of this research is that BAZNAS has prepared financial reports in accordance with PSAK Number 101.